PEMBELAJARAN MATEMATIKA SEBAGAI MEDIA PENGEMBANGAN BERPIKIR KOMPUTASIONAL - Irwan Susanto; Jesi Alexander Alim; Zetra Hainul Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In today’s highly advanced era, elementary school students are not only required to be able to perform calculations but also to possess critical and logical thinking skills. One essential skill is computational thinking, which refers to the ability to solve problems systematically, similar to how computers operate-processing and solving problems step by step. Mathematics plays a vital role in developing this ability, as mathematics learning fosters logic, reasoning, and problem-solving strategies. This article discusses the relationship between mathematics learning and the development of computational thinking among elementary school students, as well as the challenges still faced in schools. The main issue is that mathematics instruction often remains focused on mechanical computation, causing students to be less accustomed to connecting mathematical concepts with computational ways of thinking. Studies indicate that when teachers integrate computational thinking strategies into mathematics lessons, students are more likely to understand concepts deeply, demonstrate greater creativity in solving problems, and develop skills that are relevant to the demands of the 21st century. Consequently, elementary school teachers need to design mathematics lessons that not only strengthen students’ arithmetic skills but also cultivate habits of logical, systematic, and reflective thinking. In this way, mathematics can serve as a crucial foundation for developing computational thinking skills from the early stages of education.